"Chipping Away at the Issues": Piecemeal Dispute Resolution and Territorial Conflict. (January 2018) - Mattes, Michaela
Disputants might resolve their disagreements in a piecemeal fashion, addressing a subset of the issues at a time. How viable is such a strategy? I argue that partial settlements signal the desire to resolve disagreements and can lay the foundation for additional cooperation by building trust and/or demonstrating the benefits of dispute resolution. As a result, partial settlements should be associated with the resolution of remaining disagreements. Yet, scholars have questioned whether pursuing a piecemeal approach may be more harmful than helpful, and a systematic empirical test of these competing predictions is necessary. Using data from worldwide territorial claims between 1919 and 2001, I find a strong positive correlation between partial settlements and comprehensive dispute resolution. In the shorter run, partial settlements are also associated with an increased likelihood for peaceful negotiations, but there is only limited evidence that they reduce conflict before all aspects of the claim are resolved.